2010
DOI: 10.1371/journal.pone.0015100
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Airborne Influenza Virus in Aerosol Particles from Human Coughs

Abstract: Influenza is thought to be communicated from person to person by multiple pathways. However, the relative importance of different routes of influenza transmission is unclear. To better understand the potential for the airborne spread of influenza, we measured the amount and size of aerosol particles containing influenza virus that were produced by coughing. Subjects were recruited from patients presenting at a student health clinic with influenza-like symptoms. Nasopharyngeal swabs were collected from the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
402
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(432 citation statements)
references
References 18 publications
18
402
0
1
Order By: Relevance
“…Although RT‐PCR provides no indication of virus infectivity, it has been found to give a higher rate of virus detection than culture methods 17, 18, 34, 35. RT‐PCR can be used combined with culture methods to help differentiate the relative contribution to recovery efficiency by the inefficient physical removal of virus from the non‐wovens and by the natural decay of virus infectivity (e.g., desiccation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RT‐PCR provides no indication of virus infectivity, it has been found to give a higher rate of virus detection than culture methods 17, 18, 34, 35. RT‐PCR can be used combined with culture methods to help differentiate the relative contribution to recovery efficiency by the inefficient physical removal of virus from the non‐wovens and by the natural decay of virus infectivity (e.g., desiccation).…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Gralton et al .,16 breathing, coughing, sneezing, and talking can easily generate particles of a wide size range, and influenza virus has been detected in the particles generated by human respiratory activities 8, 17, 18. Therefore, we investigated the difference in viable influenza virus recovery from PPE after liquid suspension spike tests versus aerosol challenge tests.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza virus RNA has been detected in respirable airborne particles collected in healthcare facilities and other locations 9, 10, 11, 12, 13, 14, 15, 16. Influenza virus RNA also has been found in aerosol particles collected directly from infected patients while they were coughing and breathing 17, 18, 19, 20, 21, 22, 23. Six studies have demonstrated that influenza patients expel airborne particles containing viable virus 13, 18, 19, 21, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…Influenza virus RNA also has been found in aerosol particles collected directly from infected patients while they were coughing and breathing 17, 18, 19, 20, 21, 22, 23. Six studies have demonstrated that influenza patients expel airborne particles containing viable virus 13, 18, 19, 21, 24, 25. Pantelic et al .…”
Section: Introductionmentioning
confidence: 99%
“…While the importance of airborne transmission relative to direct contact is still debated, substantial evidence exists that airborne viruses pose a significant risk (Killingley and Nguyen-Van-Tam 2013). Several investigators have isolated infectious (viable, "live") IFV from ultrafine aerosols produced by infected patients (Lindsley et al 2010;Milton et al 2013;Lednicky and Loeb 2013). However, virus genomic RNA (vRNA) is more frequently detected than infectious virus.…”
Section: Introductionmentioning
confidence: 99%